Transformation of intercommunity relations and origins of communal and ethnic violence in Kandhamal - Bhatra, Robert Wilson (Social Action)
Past-independent India at the village level, witnessed how the traditional forms of origination were changing and new power relations were established in Kandhamal. The panes and the Kondhs, who for some period of time were kept or the margins of society suddenly took control of the local village council by wining Panchyat election .- Reproduced
Keywords: Conversion, Marginalisation, Communal violence, Hindustan, Christianity